Dielectric response of Mg0.95Ca0.05TiO3 ceramic filled HDPE composites with low dielectric loss. (July 2015) - Shi, Yunzhou; Zhang, Li; Yue, Zhenxing
Abstract: The Mg0.95 Ca0.05 TiO3 (MCT) 1 ceramic filled high density polyethylene (HDPE) 2 composites for microwave applications have been investigated in this paper. Composites with different volume fraction ( Vf ) 3 of ceramic fillers from 0.10 to 0.50 were prepared by twin-screw extrusion and hot pressing techniques. A descending trend of the diffraction peaks of crystalline HDPE is observed in X-ray diffraction patterns, corresponding to the ratio of ceramic filler and polymer substrate. Scanning electron microscopic photos illustrate compact samples with satisfactory uniformity. The relative permittivity ( ε r ) at microwave frequencies is found to increase with filler volume fraction. ε r of the 0.50 V f composite reaches 7.32 under its resonant frequency (8.42 GHz) while its loss tangent keeps less than 0.001. The relative permittivity of this series of composites also exhibit good frequency stability and temperature stability within the range of 10 MHz–1 GHz and −40 °C 100 °C, respectively.